Digital transformation for a sustainable future: Insights from Brazil's civil service - Sven Grimm; Wulf Reiners; Mara Braun; Laura Donath; Sophia Hörbelt; Sophie Lampert; Marcel Wich (German Institute of Development and Sustainability (IDOS), 2024)
The study investigates the governance and understanding of digitalisation for sustainability among Brazilian civil servants, emphasizing their pivotal role in leveraging digital tools to achieve the 2030 Sustainable Development Goals (SDGs). Focusing on Brazil, a global leader in digital public services and sustainability initiatives, the research explores governance approaches and perceptions among civil servants at federal and municipal levels. The study draws on qualitative and quantitative data collected from multiple cities in Brazil in 2023, employing a mixed methods approach that includes interviews, focus groups, and surveys. The findings highlight that Brazilian civil servants generally view digitalisation positively, recognizing its potential to enhance economic, social, and ecological sustainability. However, their understanding of related ecological challenges remains limited, with most knowledge gained informally through personal interest or on-the-job learning. The research also identifies key governance challenges, such as the need for system interoperability and cohesive digital policy frameworks. Key recommendations include developing targeted training programmes to address knowledge gaps, improving data protection standards, and fostering interoperability. The study also highlights opportunities for international collaboration, particularly with Germany, to share policies and develop partnerships. By shedding light on civil servants' perceptions, the research provides actionable insights for policymakers and international partners to promote a digitally enabled, sustainable future in Brazil.
Keywords: 320; Digitalisation; sustainable development; Brazil; civil service; E-Governance; E-Government; perceptions; discourse; digital policy; capacity-development